Can you see what i see?: Malaysian cultural elements in visual learning tools for children with ASD / Muhamad Hafiz Hassan ... [et al.] - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Isa, Badrul; Zulkefli, Mohd Yusof; Silah, Sumardianshah; Murwonugroho, Wegig (College of Creative Arts, 2025)
This paper presents an integrated framework for designing culturally-responsive visual learning tools for Malaysian children with Autism Spectrum Disorder (ASD). By synthesizing the ADDIE instructional design model, Fleming's VARK learning styles theory, and elements of Malaysian cultural aesthetics, we propose a comprehensive approach to creating educational materials that are both culturally relevant and effectively address the unique learning needs of children with ASD. Through qualitative analysis of existing interventions and case studies, we identify key design principles that incorporate Malaysian cultural elements while supporting the visualspatial learning strengths commonly observed in children with ASD. The resulting framework provides practical guidelines for educators and designers in developing culturally- appropriate visual learning tools that enhance engagement and learning outcomes for Malaysian children with ASD.